Synthesis, Molecular Structures and Electrochemical Investigations of [FeFe]‐Hydrogenase Biomimics [Fe2(CO)6‐n(EPh3)n(µ‐edt)] (E = P, As, Sb; n = 1, 2). Issue 42 (10th October 2019) - Ghosh, Shishir; Rahaman, Ahibur; Orton, Georgia; Gregori, Gregory; Bernat, Martin; Kulsume, Ummey; Hollingsworth, Nathan; Holt, Katherine B.; Kabir, Shariff E.; Hogarth, Graeme
Abstract : A series of ethane‐dithiolate (edt = S(CH2 )2 S) complexes [Fe2 (CO)5 (EPh3 )(µ‐edt)] and [Fe2 (CO)4 (EPh3 )2 (µ‐edt)] (E = P, As, Sb), biomimics of the core of [FeFe]‐hydrogenases, have been prepared and structurally characterised. The introduced ligand(s) occupies apical sites lying trans to the iron‐iron bond. NMR studies reveal that while in the mono‐substituted complexes the Fe(CO)3 moiety undergoes facile trigonal rotation, the Fe(CO)2 (PPh3 ) centres do not rotate on the NMR timescale. The reductive chemistry has been examined by cyclic voltammetry both in the presence and absence of CO and the observed behavior is found to be dependent upon the nature of the substituents. With L = CO or SbPh3 potential inversion is seen leading to a two‐electron reduction, while for others (L = PPh3, AsPh3 ) a quasi‐reversible one‐electron reduction is observed. Protonation studies reveal that [Fe2 (CO)5 (PPh3 )(µ‐edt)] is only partially protonated by excess HBF4 · Et2 O, thus ruling complexes [Fe2 (CO)5 (EPh3 )(µ‐edt)(µ‐H)] + out as a catalytic intermediates, but [Fe2 (CO)4 (PPh3 )2 (µ‐edt)] reacts readily with HBF4 · Et2 O to produce [Fe2 (CO)4 (PPh3 )2 (µ‐edt)(µ‐H)] + . While all new complexes are catalysts for the reduction of protons in MeCN, their poor stability and relatively high reduction potentials does not make them attractive in this respect. Abstract : A series of [FeFe]‐hydrogenase biomimics [Fe2 (CO)5 (EPh3 )(µ‐edt)] and [Fe2 (CO)4 (EPh3 )2 (µ‐edt)] (E = P, As, Sb) have been prepared and structurally characterised allowing variations in the pnictide to be systematically probed for the first time; changes to IR spectra and redox potentials being correlated with changes in the nature of the pnictide atom